INTELLIGENT GALVANOMAGNETIC CURRENT SENSORS WITH ADJUSTABLE RANGE (International journal of artificial intelligence, 2026)
This article presents the results of research on intelligent galvanomagnetic current sensors with adjustable range. Current sensors based on the galvanomagnetic effect, particularly the Hall effect, are widely used in modern electronics, automotive, industrial automation, and energy sectors. Within the scope of this research, programmable current sensors with various measurement ranges were developed and tested. The results show that the ability to adjust the amplifier coefficient and offset voltage through a digital control system enables an increase in sensor accuracy up to 0.5% and ensures effective operation across a wide measurement range (from 1A to 500A). The developed sensors feature galvanic isolation, high speed, and temperature compensation capabilities.